2009
DOI: 10.1136/gut.2008.167817
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs in plasma of patients with colorectal cancer: a potential marker for colorectal cancer screening

Abstract: MiR-92 is significantly elevated in plasma of patients with CRC and can be a potential non-invasive molecular marker for CRC screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
860
4
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,037 publications
(911 citation statements)
references
References 29 publications
(28 reference statements)
34
860
4
13
Order By: Relevance
“…Specific serum miRNA expression profiles show a great potential to serve as a novel class of biomarkers for the diagnosis of cancer and other diseases [5,6]. Numerous reports have subsequently shown that unique expression patterns of circulating miRNAs reflect various physiological and pathological conditions [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Specific serum miRNA expression profiles show a great potential to serve as a novel class of biomarkers for the diagnosis of cancer and other diseases [5,6]. Numerous reports have subsequently shown that unique expression patterns of circulating miRNAs reflect various physiological and pathological conditions [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…RNU19 or RNU6B was used as controls for tissue and cell analysis (Chen and Stallings, 2007;Liu et al, 2010). miR-16 was used as a control for the plasma analysis (Ng et al, 2009). mRNA expression of TGFb-RII and glyceraldehyde 3-phosphate dehydrogenase (internal control) was also analyzed using TaqMan qPCR system (Applied Biosystems).…”
Section: Gc Tissues and Plasma Samplesmentioning
confidence: 99%
“…Because serum and plasma are easily accessible, circulating biomarkers are one of the most promising means of diagnosis. Related studies have shown that human serum contains miRNAs and the expression pattern of these serum miRNAs can potentially be used to identify various types of cancer (Chen et al, 2008;Gilad et al, 2008;Mitchell et al, 2008;Ng et al, 2009;Resnick et al, 2009). Given that endogenous miRNAs exist in a form that is resistant to RNase activity (Patrick et al, 2008), identifying a unique serum miRNA expression in esophageal cancer can potentially assist tumor diagnosis and cancer treatment.…”
mentioning
confidence: 99%